1985
DOI: 10.1172/jci112043
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of individual superficial nephron segments to ammonium handling in chronic metabolic acidosis in the rat. Evidence for ammonia disequilibrium in the renal cortex.

Abstract: Ammonia entry along surface nephron segments of rats was studied with micropuncture techniques under control and chronic metabolic acidosis conditions. Tubule fluid was collected successively from sites at the end and beginning of the distal tubule and at the end of the proximal tubule of the same nephron. During chronic metabolic acidosis, ammonium excretion doubled. As anticipated, the ammonium concentration (TFNHO3 was significantly higher in proximal tubule fluid during acidosis, and ammonium delivery to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
55
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 32 publications
(42 reference statements)
3
55
0
Order By: Relevance
“…Indeed, BSC1 mRNA abundance significantly increased 3 h after the creation of metabolic acidosis by peritoneal dialysis, which was followed within 24 h by an augmentation of the BSC1 protein abundance (16). The augmentation of both mRNA and protein abundance persisted after 6 d of CMA induced by administration of NH 4 Cl in drinking water (16). Most important, we showed that incubation of freshly harvested MTAL fragments in an acid medium enhanced BSC1 mRNA and protein abundance (16).…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Indeed, BSC1 mRNA abundance significantly increased 3 h after the creation of metabolic acidosis by peritoneal dialysis, which was followed within 24 h by an augmentation of the BSC1 protein abundance (16). The augmentation of both mRNA and protein abundance persisted after 6 d of CMA induced by administration of NH 4 Cl in drinking water (16). Most important, we showed that incubation of freshly harvested MTAL fragments in an acid medium enhanced BSC1 mRNA and protein abundance (16).…”
mentioning
confidence: 68%
“…Chronic metabolic acidosis enhances the ability of the medullary thick ascending limb (MTAL) to absorb NH 4 ϩ at least in part by stimulating the mRNA and protein expression of BSC1/NKCC2, the MTAL apical Na ϩ -K ϩ (NH 4 ϩ )-2Cl Ϫ co-transporter. For assessing the mechanism by which an acid pH enhances the BSC1 mRNA abundance, MTAL were harvested from adrenalectomized rats and incubated in control (pH 7.35) and acid (pH 7.10) 1:1 mixtures of Ham's nutrient mixture F-12 and DME.…”
mentioning
confidence: 99%
See 3 more Smart Citations